Financial forecasting, analysis, and modelling : a framework for long-term forecasting - Samonas, Michael (John Wiley & Sons, 2015)
This book provides a complete framework of long-term financial forecasts in a practical and accessible way, helping finance professionals include uncertainty in their planning and budgeting process. With thorough coverage of financial statement simulation models and clear, concise implementation instruction, it guides readers through the entire projection plan development process. Readers learn the tools, techniques, and special considerations that increase accuracy and smooth the workflow, and develop a more robust analysis process that improves financial strategy. You will develop long-term projection plans using Excel; use appropriate models to develop a more proactive strategy; apply risk and uncertainty projections more accurately; master the Excel Scenario Manager, Sensitivity Analysis, Monte Carlo Simulation, and more. --